2002
DOI: 10.1046/j.1523-1755.2002.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of human renal D1 dopamine receptors by G protein-coupled receptor kinase 4

Abstract: These studies document the critical role of GRK4, relative to GRK2, in the homologous desensitization of D1 receptors in renal proximal tubule cells. However, the early phase of homologous desensitization is regulated by a non-GRK-mediated pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
102
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 44 publications
5
102
0
Order By: Relevance
“…Amino acid numbering is given for the human GRK family members. concurrent reduction of dopamine D1 receptor desensitization, whereas loss of GRK2 in this tissue had no effect on such desensitization [29]. Very recent studies [30] that used a short interfering RNA (siRNA) approach to decrease GRK4 activity has provided strong evidence for a specific role of GRK4 in the desensitization of GABA B receptors in cerebellar granule cells.…”
Section: Grk4mentioning
confidence: 85%
“…Amino acid numbering is given for the human GRK family members. concurrent reduction of dopamine D1 receptor desensitization, whereas loss of GRK2 in this tissue had no effect on such desensitization [29]. Very recent studies [30] that used a short interfering RNA (siRNA) approach to decrease GRK4 activity has provided strong evidence for a specific role of GRK4 in the desensitization of GABA B receptors in cerebellar granule cells.…”
Section: Grk4mentioning
confidence: 85%
“…8,43 We have reported that G protein-coupled receptor kinases (GRKs), GRK2 and GRK4, are involved in D 1 receptor phosphorylation. 44 Among the GRKs, GRK2 is most impor- tant in promoting AT 1 receptor phosphorylation. 45 It is possible that the GRK2 activation subsequent to AT 1 receptor stimulation also results in the alteration of the phosphorylation and membrane localization of the D 1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…This does not occur in SHRs because the D 1 receptor is already hyperphosphorylated and fewer D 1 receptors are found on renal cell surface membranes in SHR. 46 Although GRK4 is the major GRK regulating D 1 receptor function, 43,44 GRK4 is not involved in the desensitization of the AT 1 receptor. 47 The possibility exists that the AT 1 receptor can cause heterologous desensitization of the D 1 receptor via stimulation of effector enzymes, but it is not clear which one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like many other GPCRs, the loss of responsiveness of D1R following agonist treatment reportedly involves their phosphorylation by a variety of protein kinases, including G protein-coupled receptor kinases (GRKs) (41). A recent study by Yu et al (47) has shown that renal D1R are hyperphosphorylated and uncoupled from G proteins under basal state as well.…”
mentioning
confidence: 99%